PERTANGGUNGJAWABAN PIDANA PENCURIAN DENGAN KEKERASAN YANG MENYEBABKAN KEMATIAN OLEH SUPIR TAKSI ONLINE - Dio Nugraaha, - (2019)
Indonesia is a country that has regulations that regulate the order of the entire community by using the law, as the Indonesian Law State makes laws to create order, security, welfare and welfare for its citizens. The following are types of normative legal studies. Normative legal research on sources related to general materials which contain rules that apply noramtif which are intended to review the precautions taken by taxi drivers conducted by online taxi drivers Case Study Decisions (Case of Decision No.346 / Pid.B / 2018 / PN Cbi) which is very disturbing to the community because of committing acts of violence by carrying out this mode of launching a crime utilizing the previously designed technological advancements utilizing and utilizing transportation transportation passengers online. The problems that exist in this discussion are the accountability that exists for punishments with violence that causes death and efforts made by law enforcers to prevent and reverse these crimes. Therefore, issuing agencies that are engaged in law enforcement is harder and more accountable in handling this crime